2012
DOI: 10.1097/bpo.0b013e318257d3a9
|View full text |Cite
|
Sign up to set email alerts
|

Is Expansion Thoracoplasty a Safe Procedure for Mobility and Growth Potential of the Spine? Spontaneous Fusion After Multiple Chest Distractions in Young Children

Abstract: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…They also noted development of high thoracic kyphosis. Spontaneous fusions of ribs and vertebrae have been reported by other authors 23,24 . At least one group reported increased kyphosis magnitude and rigidity with VEPTR treatment 9 .…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…They also noted development of high thoracic kyphosis. Spontaneous fusions of ribs and vertebrae have been reported by other authors 23,24 . At least one group reported increased kyphosis magnitude and rigidity with VEPTR treatment 9 .…”
Section: Discussionmentioning
confidence: 55%
“…Despite the previously proposed benefits of the VEPTR device, recent literature suggests that serious problems may be associated with this treatment method and long-term outcomes may be less optimistic than those reported in the earlier literature [20][21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that reduced mobility (rather than complete immobilization) may be a factor in disc degeneration in human scoliosis, and may account for why expansion thoracoplasty has been associated with disc degeneration in young patients [21]. …”
Section: Discussionmentioning
confidence: 99%
“…In a biochemical study by Huber et al, the single-cell RNA sequencing of the affected site by an injury (that may apply to soft tissue injury caused by EOS surgery) revealed an early upregulation of Mesenchymal Progenitor Cell genes linked to pathways involving cell adhesion and extracellular matrix-receptor interactions leading to the development of cartilage and bone [ 19 ]. Nevertheless, autofusion has also been documented in EOS surgeries not intimately related to the spine, such as expansion thoracoplasty [ 20 , 21 ]. Betz et al [ 22 ] demonstrated that there was no significant difference in the fusion rate between two groups of adolescent idiopathic scoliosis patients who underwent posterior spinal fusion with and without graft.…”
Section: Probable Pathophysiologymentioning
confidence: 99%